The Effect of Twelve-Week Neurofeedback Training on Pain, Proprioception, Strength and Postural Balance in Men with Patellofemoral Pain Syndrome: A Double-Blind Randomized Control Trial - Mohamadreza Ahmadi; Ali Yalfani; Farzaneh Gandomi; Khosro Rashid (Shiraz University of Medical Sciences, 2020)
Background: Patellofemoral pain syndrome (PFPS) has been reported as one of the most common reasons for knee pain which accounts for about 25 % to 40% of all knee injuries. These group of patients have Postural Balance disorder that can cause pain, dysfunction in proprioception and decreased muscle strength. We aimed to study a twelve-week neurofeedback training (NFT) on pain, proprioception, strength and Postural Balance in PFPS patients. Methods: This randomized controlled trial included 32 patients with PFPS who were randomly allocated into experimental (n = 16) and control (n = 16) groups. The variables measured included pain, knee proprioception 20 and 60 degrees, muscular strength quadriceps and hip abductors and Postural Balance that were evaluated before and after intervention. The experimental group performed NFT during twelve weeks, three times per week and 30 min per session, while the control group did not receive any treatment during this time. Covariance statistical method was used for data analysis. Results: The results of data analysis showed that the experimental group had significant improvement in postural balance index anterior-posterior (p<0.004), overall stability (p<0.003), knee proprioception 20 degrees (p<0.004), knee proprioception 60 degrees (p<0.004), quadriceps muscle strength (p<0.007) and pain reduction (p<0.001). However, postural balance index medial-lateral (p>0.140) and hip abductor muscle strength (p>0.164) had no improvement after twelve weeks of NFT. Conclusions: The NFT through thalamus inhibition led to reduced pain and improved sensory pathways, sensory integrity, increased attention and cognition. They also led to improved proprioception, Postural Balance, overall stability and quadriceps muscle strength. It is suggested that future studies examine the impact of long-term and short-term NFT on the variables of the present study.